INTERVAL (investigation of NICE technologies for enabling risk-variable-adjusted-length) dental recalls trial: a multicentre randomised controlled trial investigating the best dental recall interval for optimum, cost-effective maintenance of oral health in dentate adults attending dental primary care - Clarkson, Jan E. (BMC Oral Health, 2018)
BACKGROUND: Traditionally, patients at low risk and high risk of developing dental disease have been encouraged to attend dental recall appointments at regular intervals of six months between appointments. The lack of evidence for the effect that different recall intervals between dental check-ups have on patient outcomes, provider workload and healthcare costs is causing considerable uncertainty for the profession and patients, despite the publication of the NICE Guideline on dental recall. The need for primary research has been highlighted in the Health Technology Assessment Group’s systematic review of routine dental check-ups, which found little evidence to support or refute the practice of encouraging 6-monthly dental check-ups in adults. The more recent Cochrane review on recall interval concluded there was insufficient evidence to draw any conclusions regarding the potential beneficial or harmful effects of altering the recall interval between dental check-ups. There is therefore an urgent need to assess the relative effectiveness and cost-benefit of different dental recall intervals in a robust, sufficiently powered randomised control trial (RCT) in primary dental care. METHODS: This is a four year multi-centre, parallel-group, randomised controlled trial with blinded outcome assessment based in dental primary care in the UK. Practitioners will recruit 2372 dentate adult patients. Patient participants will be randomised to one of three groups: fixed-period six month recall, risk-based recall, or fixed-period twenty-four month recall. Outcome data will be assessed through clinical examination, patient questionnaires and NHS databases. The primary outcomes measure gingival inflammation/bleeding on probing and oral health-related quality of life. DISCUSSION: INTERVAL will provide evidence for the most clinically-effective and cost-beneficial recall interval for maintaining optimum oral health in dentate adults attending general dental practice. TRIAL REGISTRATION: ISRCTN95933794 (Date assigned 20/08/2008).